ANÁLISIS DE LA IDONEIDAD DIDÁCTICA EN LA ENSEÑANZA DE LA FUNCIÓN LOGÍSTICA: UN ESTUDIO DE CASO EN LA ESCUELA SECUNDARIA - Rodríguez, Claudio (2026)
This study investigates the didactic suitability in mathematics teaching through the use of the logistic function to model population growth among secondary school students. It is based on the Ontological and Semiotic Approach to Mathematical Knowledge and Instruction (EOS), using tools from this framework to assess students' practices and mathematical understanding. A qualitative methodology was employed, involving the design and validation of an inquiry instrument, implemented with fifth-year secondary school students. The results indicate that the logistic function provides a more comprehensive and realistic understanding of population growth phenomena, enabling students to develop critical and analytical competencies in mathematics. The importance of integrating Logistic Function into the Secondary school curriculum is highlighted to promote meaningful and contextualized learning.